Anisotropic Plasmonic Effect on Ag Nanoparticles under Microwave‐Induced Plasma‐in‐Liquid: Insight into Growth Mechanism. (26th December 2021) - Bharti, Amardeep; Bhardwaj, Richa; Goyal, Navdeep
Abstract: Anisotropic nanoparticles are a potential foundation for emerging materials engineering having anomalous properties often to an extraordinary degree‐enabling widespread new applications. In the bottom‐up approach, isotropic nanoparticles are formed by self‐assembly following the basic packing rule but lack directional interaction. On the other hand, anisotropic nanoparticles involve complex programmability having directional interaction and thus become of utmost interest in science and technology. In this paper, the anisotropic plasmonic effects in silver (Ag) nanoparticles under microwave‐induced plasma‐in‐liquid‐assisted decomposition of saccharides and di‐saccharides following the green chemistry process are investigated. The effect of microwave power, irradiation time, and relative chemical composition has been investigated in detail using extinction spectroscopy and Mie theory. The relationship between extinction curve shape parameter (S) and Mie theory has been established. The extinction spectroscopy and transmission electron microscopy (TEM) study confirm the existence of anisotropic plasmonic effects in Ag nanoparticles following two‐generation growth mechanisms having an average particle size of 2 and 32 nm. This technique offers rapid (20–40 sec) bulk production and is cost/energy effective than the conventional synthesis route. Abstract : The anisotropic growth of metal nanoparticles under controlled microwave‐induced plasma‐in‐liquid assisted decomposition of saccharides and disaccharides following the green chemistry process are successfully achieved. The growth of nanoparticles involves two‐generation process having an average particle size of 2 and 32 nm. A correlation between extinction curve shape‐parameter and Mie‐theory is established that leads to time‐resolved analysis.